Predictive and Prognostic Value of DNA Damage Response Associated Kinases in Solid Tumors - Gachechiladze, Mariam; Skarda, Josef; Bouchalova, Katerina; Soltermann, Alex; Joerger, Markus (Frontiers in Oncology, 2020)
Dysfunctional DNA repair with subsequent genome instability and high mutational burden represents a major hallmark of cancer. In established malignant tumors, increased DNA repair capacity mediates resistance to DNA-damaging agents such as cytotoxic drugs, radiotherapy and selected small molecules including inhibitors of PARP, ATM, ATR and WEE1. On the other hand, DNA repair deficiency is not only associated with sensitivity to selected anticancer drugs, but also with increased mutagenicity and increased neoantigen load on tumor cells, resulting in increased immunogenicity and improved response to CTLA4- or PD-(L)1 targeting monoclonal antibodies. DNA damage response (DDR) is a complex signal transduction pathway which senses DNA damage, tranduces signals to the cell, influences cellular responses to DNA damage, and activates DNA repair pathways. DNA double strand breacks (DSBs) are the most deleterious form of DNA damage. Tumor cells are characterised by frequent acumulation of DSBs caused by either endogenous replication stress or the impact of cancer treatment, most prominently chemotherapy and radiotherapy. Therefore, response of cancer cells to DSBs represents a crucial mechanism for how tumors respond to systemic treatment or radiotherapy, and how resistance develops. Ample clinical evidence supports the importance of DDR associated kinases as prognostic and predictive biomarkers in cancer patients. The ATM-CHK2 and ATR-CHK1-WEE1 pathways initiate DNA DSB repair. In the current review, we focus on major DDR associated kinases including ATM, ATR, CHK1, CHK2 and WEE1, and discuss their potential prognostic and predictive value in solid malignancies.